NILAI-NILAI ADAT MINANGKABAU DALAM NOVEL MEMANG JODOH KARYA MARAH RUSLI - Agustin, Rika; Bahardur, Iswadi; Mana, Lira Hayu Afdetis (Pendidikan Bahasa Indonesia, 2014)
Indeed Houses, a novel set in Minangkabau calture that many tradisional Minangkabau describe the problem. This study was conducted to describe the traditional Minangkabau values contained in the novel. This research is a qualitative descriptive method. This research is used to describe the data contained in the novel. Data collocted by the steps: (1) read and understand the novel, (2) quotation marks, (3) inventory of data, (4) to classify the data. Based on the description of the data and the results of this study concluded that the traditional Minangkabau values contained in the novel, namely, marriange matrilineal, mamak roles and marriagebetween ethnic groups in Indonesia. (1) matrilineal marriage is a marriage with close relative such as child marriage with the niece or home kebako. (2) mamak role in Minangkabau is a guard treasures and meet all the needs of his nephew, such as school fees, and matrilineal problems. (3) inter-ethnic marriages are prohibited in Minangkabau in Indonesia because it can damage the system and the pattern of Minangkabau customs.